Palm oil export diversification in Peru 2013 – 2022 - Bardales Llatas, Gian Pier; Heredia Llatas, Flor Delicia (LACCEI, 2024)
Peru could become one of the main exporters of palm oil globally, taking into account that the Peruvian state encouraged this initiative since the palm serves as a crop that helps eradicate the coca leaf plantation. The objective was to analyze the level, basic indicators, diversification of the main destination countries and exporting companies of palm oil in Peru from 2013-2022. The study had a basic methodology with a quantitative approach, with a non-experimental, transversal descriptive scope, using the Herfindalh Hirschman index, since the information by AZATRADE was observed, to identify the reports by the period of exports, resulting in Peru , in recent years the international marketing of palm oil has increased with a report in 2022 of 50,254,582 in FOB USD value, costing 1.44 per KG, Chile being its main destination country followed by Guatemala, finding Industria del Espino S.A. and Alicorp S.A.C. as its main exporting companies. It was concluded that, apart from the 11% increase in exports, Peru has a concentrated market, with Chile and Guatemala being dependent